Longevity biotechnology: bridging AI, biomarkers, geroscience and clinical applications for healthy longevity. - Lyu,Y-X; Fu,Q; Wilczok,D; Ying,K; King,A; Antebi,A; Vojta,A; Stolzing,A; Moskalev,A; Georgievskaya,A; Maier,AB; Olsen,A; et al. (Aging (Albany NY), 2024)
The recent unprecedented progress in ageing research and drug discovery brings together fundamental research and clinical applications to advance the goal of promoting healthy longevity in the human population. We, from the gathering at the Aging Research and Drug Discovery Meeting in 2023, summarised the latest developments in healthspan biotechnology, with a particular emphasis on artificial intelligence (AI), biomarkers and clocks, geroscience, and clinical trials and interventions for healthy longevity. Moreover, we provide an overview of academic research and the biotech industry focused on targeting ageing as the root of age-related diseases to combat multimorbidity and extend healthspan. We propose that the integration of generative AI, cutting-edge biological technology, and longevity medicine is essential for extending the productive and healthy human lifespan.